BPBD STRATEGY IN RESPONDING TO TORNADO DISASTERS IN KENDARI CITY, SOUTHEAST SULAWESI PROVINCE (JISIPOL | Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Tornadoes are one of the most common types of hydrometeorological disasters, occurring suddenly and potentially causing physical damage, material losses, and disruption to community activities. The city of Kendari, with its diverse geography and topography, is vulnerable to such disasters and therefore requires effective disaster management strategies. This study aims to analyze the strategies of the Kendari City Regional Disaster Management Agency (BPBD) in managing tornadoes, identify factors that hinder their implementation, and examine efforts made to overcome these obstacles. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through in-depth interviews, field observations, and documentation. Research informants included BPBD leaders, sub-district and village government officials, and communities affected by disasters. The results showed that the Kendari City BPBD's strategy had been implemented through disaster awareness campaigns, the formation of disaster preparedness groups, cross-sector coordination, and mitigation and emergency response efforts. However, the implementation of these strategies has not been optimal due to limited facilities and infrastructure, a lack of human resources, and the uneven distribution of disaster preparedness groups at the village level. Efforts made by the BPBD to overcome these obstacles include increasing awareness, strengthening inter-agency coordination, and proposing the addition and improvement of disaster management facilities and infrastructure. This study concludes that strengthening resources, policy and budgetary support, and institutional synergy are key factors in improving the effectiveness of tornado disaster management strategies in Kendari City.